THE INFLUENCE OF PERCEIVED VALUE, PRODUCT ACCESSIBILIT, AND PROMOTER RESPONSIVENESS ON THE PURCHASE DECISION OF MOBILE PHONES AT SMS SHOP MIJEN SEMARANG - Devi Lilis Mardiyani; Sri Martono (LPPM Universitas An Nuur, 2024)
Background & Purpose: Competition in the retail world, particularly in mobile phone sales, is becoming increasingly intense due to the rising number of competitors and product variations. Companies like SMS Shop Mijen Semarang need to enhance the performance of their promoters to ensure effective operations and satisfactory customer service. This study aims to analyze the influence of perceived value, product accessibility, and promoter responsiveness on purchasing decisions for mobile phones at SMS Shop Mijen, Semarang. The perceived value variable is measured through emotional, social, functional values, and price/value for money, while product accessibility is assessed based on distance, travel costs, and time required to reach the store. Promoter responsiveness is evaluated based on their ability to meet consumer needs. Methode :The method used is quantitative with a survey approach, collecting data from 68 consumers through questionnaires. The data is analyzed using multiple linear regression. Result: The results indicate that all three variables significantly influence purchasing decisions, and it is recommended that SMS Shop Mijen enhance the functional value of its products and ensure promoters remain responsive to consumer needs. Conclusion & Suggestion: Therefore, perceived value, product accessibility, and promoter responsiveness significantly influence purchasing decisions for mobile phones at SMS Shop Mijen, Semarang. This research serves as a foundational study, and future research should expand on this model by exploring additional variables and conducting a more comprehensive analysis to further understand the factors affecting purchasing decisions